Weight Control Program and Gestational Weight Gain in Disadvantaged Women with Overweight or Obesity: A Randomized Clinical Trial. Issue 3 (21st February 2018) - Cahill, Alison G.; Haire‐Joshu, Debra; Cade, W. Todd; Stein, Richard I.; Woolfolk, Candice L.; Moley, Kelle; Mathur, Amit; Schechtman, Kenneth; Klein, Samuel
Abstract : Objective: This study aimed to evaluate the efficacy of a home‐based lifestyle intervention delivered through Parents as Teachers (PAT) to reduce excessive gestational weight gain (GWG). Methods: This was a single‐blinded randomized controlled trial conducted as part of the LIFE‐Moms consortium at a single university‐based tertiary care institution from October 2012 to March 2016. There were 267 socioeconomically disadvantaged (SED) African American women with overweight or obesity (BMI 25.0‐45.0 kg/m 2 before pregnancy. Participants were randomized to therapy with standard PAT alone ( n = 134) or PAT plus a lifestyle intervention program embedded within the standard PAT program (PAT+) ( n = 133). Both interventions were delivered in 10 biweekly home visits during pregnancy. The primary outcome was the percentage of women whose GWG exceeded the Institute of Medicine guidelines, and secondary outcomes included both weekly and total GWG. Results: Compared with the standard PAT group in the intent‐to‐treat analysis, the PAT + group gained less weekly (0.4 kg vs. 0.5 kg/wk; P = 0.04) and total (8.0 kg vs. 9.6 kg; P = 0.02) weight during gestation. Fewer participants in the PAT + group had excessive total GWG (36.1% vs. 45.9%), but the difference between groups was not statistically significant ( P = 0.11). Conclusions: PAT + reduced the weekly and total GWG in SED African American women with overweight or obesity at the start of pregnancy.